O signo “segurança pública” na matriz curricular unificada da SENASP: condições de produção e efeitos de sentido - Ferreira, Deyvid Braga (2012)
This inquiry has aim is investigated which by the effects of sense of changes brought by the Womb Curriculum national for the formation of the professional in public security in Brazil, from the analysis of the official speech that preaches “ public security with citizenship ”. Our hypotheses are that the proposals contained in the Womb Curricular United indicate a tendency of subservience to the dictates of the capital, besides which the Ideological Positions that permeated the preparation of the Womb Curricular show an attempt of re-signification of the signs of the public security. Ours theoretician docks and methodology it is based on the historical dialectic materialism (MARX & ENGELS: 2006, 2007; MARX, 2006; MÉSZÁROS: 2007, 2008, 2009; LESSA, 2006; TONET, 2009 e TONET & LESSA 2004) and in the Analysis of the Speech of French Line, in order to analysis the picture of historical evolution of as the right to public security was inserted in our constitution. With this, we will be able to reveal what really means the public present security in the womb curriculum of the SENASP/MJ. The obtained result showed us that it is unequal such a concept in the womb curricular and in the police Brazilian teaching. With this, such a womb camouflages the precariousness of the work in public security, imposing on the workers the dictates of the capital, turned to the agreements neoliberalism and values of precariousness of his work.